Pengaruh Mengakses Korean Wave terhadap Perilaku Imitasi Remaja di Kota Palu - Isnaini Nurul Lathifah; Achmad Herman; Muh. Isa Yusaputra (Kanal: Jurnal Ilmu Komunikasi, 2018)
This study aims to determine the effects of Korean wave access activities that include: duration (X1), frequency (X2), attention (X3) to imitation behavior (Y) teenagers in Palu City. The researcher theory used Social Learning Theory. The study used survey method that used sample size from a population, with the number of samples were 73 students SMKN 1 Palu that represent few of teenagers in Palu City. This study used questionnaire as the main data collection tool and the method of analysis used multiple linear regression analysis. Based on the results of the coefficient of determination output (R2) obtained Adjust R Square (R2) in 0.740 or 74%. This result showed that the percentage was influence of X variable (duration, frequency, attention) in accessing Korean Wave through variable y (imitation behavior) teenagers in Palu that was 74%. Thus, the hypothesis Ha accepted and Ho rejected.